Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1971
DOI: 10.4141/cjss71-006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Nitrogen in the Soil as a Means of Predicting the Fertilizer Nitrogen Requirements of Barley

Abstract: It 22 field trials, over a seven-year period, highly signifi.cantly^corr-elated with the uptake iigftfy iig"ln"ant torrelations weie fou-nd be-oiniirogen, the -l value being O.86' These tw"eeri niirate nitrogen to various depths in data, combin.ed-with.a factor for the efficiency the ioiiprofile at seiding time and the-uptake of uiilization of a nitrogenous fertilizer, were oi "it.-o!"" by th" aboie-ground portidn of used to derive an equation which predicls the turt"V u"t tru*".t.-Tht be;t correiatiotr *as am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…The approach used by soil testing institutions in Saskatchewan is to consider both sources of N as equally efficient (Saskatchewan Soil Testing Laboratory 1990). Nevertheless, the relative efficiency of N S with respect to N F determined in our model is in agreement with studies that have shown that on average only 60% of N F banded in the spring is available to the crop under Canadian prairie conditions (Soper et al 1971;Grant et al 1991). In moister environments, recovery of fertilizer N applied in the spring to winter wheat ranges from 51 to 68%, depending on early spring rainfall (Powlson et al 1986).…”
Section: Grain Yield Response To N and Available Watersupporting
confidence: 77%
“…The approach used by soil testing institutions in Saskatchewan is to consider both sources of N as equally efficient (Saskatchewan Soil Testing Laboratory 1990). Nevertheless, the relative efficiency of N S with respect to N F determined in our model is in agreement with studies that have shown that on average only 60% of N F banded in the spring is available to the crop under Canadian prairie conditions (Soper et al 1971;Grant et al 1991). In moister environments, recovery of fertilizer N applied in the spring to winter wheat ranges from 51 to 68%, depending on early spring rainfall (Powlson et al 1986).…”
Section: Grain Yield Response To N and Available Watersupporting
confidence: 77%
“…Pre-plant soil NO 3 -N is often used to estimate available soil N under semiarid conditions (Soper et al 1971;Bole and Pittman 1980;Grant et al 1991a). Pre-plant soil NO 3 -N was generally 20 to 40 kg N ha -1 less than unfertilized crop N uptake in Alberta studies, but deviations of more than 50 kg N ha -1 were not uncommon (McKenzie et al 2004a, b).…”
Section: Nitrogen Fertilizermentioning
confidence: 99%
“…The meadow fescue suffered more water stress from drought than did the barley, as a result of its much shallower root system (Hansson and Andr~n, 1987). A literature survey of comparable field experiments, i.e., those on barley fertilized with 10-12gNm -2 as calcium-nitrate or ammonium- nitrate showed a first-year export during harvest of 45-55% of the added fertilizer (Dowdell et al, 1984;Gasser and Iordanou, 1967;Kjellerup and Dam Kofoed, 1983;N~rlund et al, 1985;Soper et al, 1971). Export figures in our investigation (55-64%) slightly exceeded that range.…”
Section: Nitrogen In Harvestmentioning
confidence: 99%